PEMANFAATAN POTENSI TENAGA AIR DI SALURAN IRIGASI BANJARCAHYANA, KABUPATEN BANJARNEGARA, PROPINSI JAWA TENGAH SEBAGAI USAHA PENGURANGAN EMISI GAS RUMAH KACA - Irhan Febijanto (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2008)
This study was conducted by collaboration between BPPT, Chugoku Electric Power, and PT Indonesia Power and funded by GEC (Japan-Geo Environment Center). The study was started on August 2005, and finished on September 2006. The purpose of the study was to explore the unutilized potentials micro hydro power plants (MHPP) in Banjarcahyana irrigation channel. These sites are located at south eastern of Banjarnegara city. Development of these MHPP will be planned put into Clean Development Mechanism (CDM), therefore operation of these power generation would be calculated to reduce global warming effects. According to the study result, it was found eight locations having potential to build as MHPP. The development of the project economically feasible estimated could reduce 17,252 t-CO2 of Green House Gas Effect annually. This study also provides new emission coefficient factor for electricity grid system of Jawa Bali Madura (JAMALI).